Efinaconazole: DoE-supported development and validation of a quantitative HPTLC method and its application for the assay of drugs in solution and microemulsion-based formulations. Issue 10 (28th February 2020) - Patel, Rashmin B.; Patel, Mrunali R.; Patni, Nikesh R.; Agrawal, Vikas
Abstract : Herein, a simple and rapid HPTLC method using densitometric analysis was developed and validated for the assay of efinaconazole in pharmaceutical formulations (solution and microemulsion). Abstract : Herein, a simple and rapid HPTLC method using densitometric analysis was developed and validated for the assay of efinaconazole in pharmaceutical formulations (solution and microemulsion). The chromatographic conditions such as the concentration of the organic phase, chromatographic chamber saturation time and development distance were optimized to obtain a retardation factor ( R f ) value in an acceptable range (0.2 < R f < 0.8) using the Box–Behnken experimental design to develop a robust HPTLC method for the assay of efinaconazole. Using the different solutions provided for optimization by the Design Expert 8.0 software, experimental conditions with a desirability of 1 or near to 1 were selected. Based on the criteria for efinaconazole with R f between 0.2 to 0.8, a desirability of 1 was obtained, which gave the optimal composition of methanol in the mobile phase together with toluene (9.0 : 1.0 v/v), development distance of 72 mm and chamber saturation time of 18 min. The optimized method was validated according to the ICH Q2(R1) guidelines, and statistical analysis proved that the method is robust, specific (peak purity ≥ 0.9999), sensitive (LOD of 26.09 ng and LOQ of 78.29 ng), accurate (98.62–100.40%) and precise (% RSD < 2.0 for efinaconazole). Thus, the proposed HPTLC method provides a simple and cost-effective tool for the routine quantitative estimation of efinaconazole in quality control laboratories.